Literature Review: Potential of Secang Wood (Caesalpinia Sappan L) Decoction on Lowering Blood Pressure in Hypertension Sufferers - Mira Nurazizah; Popi Sopiah; Rafika Rosyda (LPPMPK- Universitas Muhammadiyah Cileungsi, 2024)
Known as the silent killer because it frequently has no symptoms, hypertension, also known as high blood pressure, is a condition of the heart and blood vessels marked by a rise in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. The World Health Organization reports that Indonesia is seeing an increase in hypertension patients. According to Riskesdas data, West Java is the second-most hypertensive province, with 39.6% of cases, behind South Kalimantan's 44.1%. Indonesia still has a high rate of hypertension, making it a public health issue. Antihypertensive medications are one method that hypertension patients utilize to control or treat their condition. However, using too many chemicals or medications over an extended period of time can have negative health effects and be rather expensive. There are further methods of treating hypertension, such as administering secang wood decoction, which has strong antioxidant effects and lowers blood pressure in hypertensive individuals. Using the narrative review model and the literature review approach, we searched for relevant articles both domestically and globally using Google Scholar and PubMed. which only includes 4 journals that meet the sample inclusion criteria and the last 8 years, from 2016 to 2023. Additionally, the articles used as samples were listed in a table and described in detail to clarify the current approaches. This research review's conclusion is that secang wood decoction can be utilized to treat hypertension in patients, in addition to treating diarrhea, fighting cancer, and decreasing cholesterol